2004
DOI: 10.2337/diabetes.53.3.861
|View full text |Cite
|
Sign up to set email alerts
|

Association of the VEGF Gene With Proliferative Diabetic Retinopathy But Not Proteinuria in Diabetes

Abstract: Diabetic retinopathy and nephropathy cause significant morbidity in patients with diabetes. Vascular endothelial growth factor (VEGF) is a potent angiogenic and vascular permeability factor and is implicated in both of these diabetes complications. We previously reported transfection studies showing the VEGF ؊460 and VEGF ؉405 polymorphisms to increase basal VEGF promoter activity by 71% compared with the wild-type sequence. Therefore, we investigated the association of these VEGF polymorphisms with proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
100
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(107 citation statements)
references
References 21 publications
4
100
3
Order By: Relevance
“…Three studies (25,27,28) investigated rs2010963, a promoter variant, of which two studies were performed in type 2 diabetes (27,28) and one in both type 1 and type 2 diabetes (25). Two studies (25,28) found no association between this SNP and diabetic retinopathy. While rs2010963 (C on the forward strand) approached nominal significance with time to severe retinopathy in the DCCT/EDIC probands in our single-marker analysis (HR 1.21 [95% CI 0.98 -1.50], P ϭ 0.078), it was not retained in backward or forward selection models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies (25,27,28) investigated rs2010963, a promoter variant, of which two studies were performed in type 2 diabetes (27,28) and one in both type 1 and type 2 diabetes (25). Two studies (25,28) found no association between this SNP and diabetic retinopathy. While rs2010963 (C on the forward strand) approached nominal significance with time to severe retinopathy in the DCCT/EDIC probands in our single-marker analysis (HR 1.21 [95% CI 0.98 -1.50], P ϭ 0.078), it was not retained in backward or forward selection models.…”
Section: Discussionmentioning
confidence: 99%
“…Several cross-sectional studies have investigated the genetic involvement of VEGFA in diabetic retinopathy (25)(26)(27)(28)(29). Three studies tested rs833061 (Ϫ460) for association with diabetic retinopathy in patients with type 2 diabetes (25-27): one observed an association with the C-allele and the C/C genotype (25), another found association with the C/T genotype (26), whereas the third one found no association (27).…”
Section: Research Design and Methods-a Total Of 1369 Caucasian Subjementioning
confidence: 99%
See 1 more Smart Citation
“…thiolactone) increase the expression of the vascular endothelial growth factor (VEGF) in cell cultures via activation of its transcription (Maeda et al 2003a;Roybal et al 2004). The VEGF is a pro-angiogenic factor known to play a key role in the development and progression of DR (Roybal et al 2004;Ray et al 2004). For these reasons, it may be readily postulated that the C677T MTHFR gene polymorphism might be involved in the development of DR.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF seems to be important for the formation of ascites and pleural effusion in advanced cancer patients (11,12). Moreover, VEGF expression is associated with the abnormal angiogenesis that occurs in diabetic retinopathy (13) as well as with several kinds of cancers, such as colorectal, gastric, pancreatic, breast, prostate, lung, and melanoma (14 -20). In the clinical setting, bevacizumab, a recombinant humanized monoclonal antibody to VEGF with efficacy against colorectal and other malignancies, has already been approved for patients (21).…”
mentioning
confidence: 99%